Redescription of hemiurid species parasitic in marine fishes from Ha Long bay, Vietnam - Ha, Nguyen Van; Ngo, Ha Duy; Binh, Tran Thi; Hung, Nguyen Manh; Hien, Hoang Van (Academia Journal of Biology, 2012)
The present paper redescribed four trematode species, which are new records for Vietnam, such as: Hemiurus arelisci Yamaguti, 1938; Stomachicola muraenesocis Yamaguti, 1934; Lecithochirium alectis Yamaguti, 1970 and Merlucciotrema praeclarum (Manter, 1934) Yamaguti, 1971 (family Hemiuridae Looss, 1899). All the trematodes are illustrated and some problems concerning their geographical distribution are discussed. H. arelisci from Scomberoides lysan (Doublespotted queenfish) is characterized mainly by seminal vesicle constricted into two portions; ecsoma well developed; pars prostatica tubular, long. Characteristic features of S. muraenesocis (host: Indian pike conger Congresox talabonoides) are body very long; ecsoma enormous; seminal vesicle oval, in hindbody; pars prostatica tubular, long; majority of uterine coils within ecsoma, normally fill less than half of ecsoma. Characteristic features of L. alectis (host: Yellow drum - Nibea albiflora) are body surface smooth; seminal vesicle in forebody; vitellarium two lateral masses, divided into three and four digitiform lobes. M. praeclarum from Platycephalus indicus (Bartail flathead), Elentheronema tetradactylum (Fourfinger threadfin fish) is characterized mainly by ecsoma well developed; body surface smooth; seminal vesicle in forebody; vitelline lobes digitiform.